Brand Ambassador Can Moderates The Influence of Rating Reviews on Purchasing Decisions : Penelitian - Kushariyadi; Muslihatul Hidayah; Dona Katarina; Ede Rohimat; Sherly Ernawaty Suanto (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
This study aims to analyze and explain the moderating role of Brand Ambassadors in the relationship between Rating Reviews and Consumer Purchase Decisions on e-commerce platforms . In the digital era, consumers rely heavily on information from other users in the form of ratings and reviews to reduce the risk of uncertainty. However, the effectiveness of these reviews is often influenced by the credibility of public figures representing the brand. The research method used is quantitative with a survey approach to active marketplace users in Indonesia. Data analysis was conducted using Structural Equation Modeling (SEM) with the help of SmartPLS software. The results are expected to show that Rating Reviews have a positive and significant influence on Purchase Decisions. Furthermore, this study examines whether the presence of Brand Ambassadors with high congruence can strengthen the positive influence of good ratings or actually mitigate the impact of low ratings. These findings provide theoretical contributions to the digital consumer behavior literature and managerial implications for companies in allocating marketing budgets between developing customer review systems and contracting celebrities as brand ambassadors.